A GRAMMAR OF THE CORPSE: NECROEPISTEMOLOGY IN THE EARLY MODERN MEDITERRANEAN BY ELIZABETH SPRAGINS (REVIEW) - Sierra Matute, Víctor (ConSecuencias, 2024)
Elizabeth Spragins’ recent book offers a compelling exploration of the often-overlooked relationship between corporeality and knowledge in early modern studies. As I have noted elsewhere, our field frequently neglects the material contingency of the objects we examine, often gravitating toward the abstraction that the nature of language itself seems to invite. Yet, Spragins skillfully persuades us to decline this invitation, urging instead a return to the materiality of the dead body as a site of knowledge production. As the title aptly suggests, A Grammar of the Corpse: Necroepistemology in the Early Modern Mediterranean reveals that language is not only made of abstract words, but also of flesh, bones, joints, and the decaying remnants of human existence, all bound up in the processes of knowing. Spragins guides us through her research process over the past few years in a preface that, in itself, encapsulates all the elements we will encounter throughout the book. Her eureka moment occurred when she found herself before the manuscript of El diálogo de Jesucristo con una calavera, preserved in the Colegio Escuelas Pías in Zaragoza. This Aljamiado codex—that is, a document written phonetically in a Romance language such as Aragonese, but using Arabic script—emerged during Spragins’ quest for spirits in early modern literature. Yet, time and again, she stumbled upon texts that foregrounded the materiality of the body rather than the spectrality of the ghost. Spragins’ book analyzes this early modern fixation through a sophisticated theoretical approach that combines new materialism, historical research, affect theory, and philology. In order to navigate the vast number of early modern texts in which the dead body assumes a central role, Spragins narrows her focus to works connected to a specific historical event: the Battle of al-Qaṣr al-Kabīr (1578), or Alcazarquivir, in present-day northwestern Morocco. According to various versions of the legend, Sebastian, the King of Portugal, either died in battle and his dead body went missing, or he disappeared and was believed to still be alive, destined to return one day. The debate surrounding the king’s body is accompanied by the immense number of deaths caused by the battle, frequently represented in the texts that recount it. This ideologically charged moment, often recognized as a catalyst for the establishment of the Iberian Union, serves as the historical anchor for Spragins’ analysis. A Grammar of the Corpse is a bold undertaking that seeks to transgress the academic conventions of early modern studies by weaving together Arabic, Aljamiado, Portuguese, and Spanish texts, disrupting the traditional geographies of our field, and integrating diverse critical approaches. This transgressive spirit is also reflected in the book’s inventive structure: while the introduction offers a comprehensive exploration of “necroepistemology” in the early modern Mediterranean, with transatlantic connections, each of the five chapters focuses on a key concept and addresses a question related to necroepistemology as it appears in the battle’s narratives—“presence” (where?), “absence” (when?), “vitality” (who?), “assemblage” (with whom?), and “erasure” (what?). Perhaps the only drawback of this approach is that, by navigating multiple fields—Middle Eastern Studies, Hispanism, Mediterranean Studies, Medieval and Early Modern Iberianism, Transatlantic and Transoceanic Studies, as well as archive and affect theory—it risks not immediately catching the attention of those interlocutors who could greatly benefit from Spragins’ analysis and methodologies. May this brief review serve as an invitation for all of them to engage with this incredibly remarkable work.